2014
DOI: 10.1007/s10517-014-2675-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin-18 in Destabilization of the Atherosclerotic Plaque in Humans

Abstract: Precise location of IL-18 in cell and tissue elements of the atherosclerotic lesions in humans and its role in destabilization of the atherosclerotic plaque were detected. The data suggested a hypothesis on indirect involvement of IL-18 in destruction of the elastic and collagen fibers in an unstable plaque due to this cytokine capacity to induce the production of IFN-γ in T cells and macrophages, this eventually leading to inhibition of collagen and elastin synthesis in smooth muscle cells of the vascular wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…These authors have precisely demonstrated the location of IL-18 in the cellular and tissue elements of unstable and stable atherosclerotic plaques, whereas no IL-18 was observed in control vascular tissue. Intracellular (endotheliocytes, macrophages/monocytes) and diffuse extracellular IL-18 was shown to be located mainly in unstable lesions [37], which clearly demonstrated the importance of IL-18.…”
Section: Interleukin-18 As a Mediator In The Pathophysiology Of Athermentioning
confidence: 78%
See 2 more Smart Citations
“…These authors have precisely demonstrated the location of IL-18 in the cellular and tissue elements of unstable and stable atherosclerotic plaques, whereas no IL-18 was observed in control vascular tissue. Intracellular (endotheliocytes, macrophages/monocytes) and diffuse extracellular IL-18 was shown to be located mainly in unstable lesions [37], which clearly demonstrated the importance of IL-18.…”
Section: Interleukin-18 As a Mediator In The Pathophysiology Of Athermentioning
confidence: 78%
“…In an another study, the myocardium of patients with ischemic heart failure express the alpha chain of the IL-18 receptor and have elevated levels of circulating IL-18 levels and has been shown to be correlated with death [15]. Very recently, [37] have demonstrated role of interleukin 18 in destabilization of the atherosclerotic plaque in humans. These authors have precisely demonstrated the location of IL-18 in the cellular and tissue elements of unstable and stable atherosclerotic plaques, whereas no IL-18 was observed in control vascular tissue.…”
Section: Interleukin-18 As a Mediator In The Pathophysiology Of Athermentioning
confidence: 97%
See 1 more Smart Citation
“…Specifically, IL-18 induces T cells and natural killer (NK) cells to produce IFN-γ and promotes the differentiation of T cells into Th1 cells to enhance the cell-mediated immune response. In addition, IL-18 induces the expression of IL-8, TNF-α, and adhesion molecules, which promote atherosclerotic plaque rupture [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is associated with presence of carotid plaques and plaque instability (26, 38,41). There are some hypothesis that IL-23 and IL-27 are also increased in carotid atherosclerosis (42,43) and IL-18 is connected with plaque destabilization (44). Still their role and action in the inflammation and plaque development is not clear.…”
Section: Ofmentioning
confidence: 99%